The inhibitory effect of some pyrazole ligands and their Cu(II) complexes on the growth of Escherichia coli, Klebsiella–Enterobacter spp., and Staphylococcus aureus - Zaimović, Majda Šahman; Kosović Perutović, Milica; Jelušić, Gordana; Radović, Ana; Jaćimović, Željko (Frontiers in Pharmacology, 2022)
The aim of this study was to evaluate the inhibitory activity of chemistry prod-ucts, against growth of Escherichia coli, Klebsiella-Enterobacter spp. and Staph-ylococcus aureus. Pyrazole derivatives (4-Bromo-2-(1H-pyrazol-3-yl)phenol, 4-Nitro-3-pyrazolecarboxylic acid, N-(Benzyloxycarbonyl)-1H-pyrazole-1-carboxamidine), 3-amino-5-hydroxypyrazole, 3,5-Pyrazoledicarboxylic acid monohydrate and se-lected complexes of Cu(II) with mentioned pyrazoles as ligands were used as chemistry bioactives for antibacterial activity. The testing method was carried out according to the disk diffusion method. Some of compounds have showed inhib-itory effect against the growth of E. coli, a small number of compounds have showed inhibitory effect against the growth of Klebsiella-Enterobacter spp., but did not show an inhibitory effect on Staphilococcus aureus, compared to amoxi-cillin as a standard.Introduction